Masters of Russian Animation - Volume 3 - Norstejn, Jurij Borisovic; Nazarov, Eduard; Chitruk, Fëdor Savel'evic; Gorlenko, Aleksandr (image Entertainment, 2000)
An extraordinary collection of award-winning animated short films by Russia's world-renowned directors and artists. Digitally restored from 35mm materials newly printed by the National Film Archive of Russia, these are the highly personal animated short films from the Soyuzmultfilm Studio. Produced from 1979 through 1985, this volume of films, many of which received highest honors at international film festivals, are each unique, crafted artistically and intellectually. [www.amazon.com]